Equilibrium, Thermodynamic and Kinetic Study of the Adsorption of a New Mono Azo dye onto Natural Iraq Clay - Alya Khider Abaas (Journal of Global Pharma Technology, 2018)
In the present work, bentonite clay was used as an adsorbent for the removal of a new prepared mono azo dye, 4-[6-bromo benzothiazolyl azo] thymol (BTAT) using batch adsorption method. The effect of many factors like adsorption time, adsorbent weight, initial BTAT concentration and temperature has been studied. The equilibrium adsorption data was described using Langmuir and frundlich adsorption isotherm. Based on kinetics study, it was found that the adsorption process follow pseudo second order kinetics. Thermodynamics data such as Gibbes Free energy ∆Gᵒ, entropy ∆Sᵒ and ∆Hᵒ were also determined using Vant Hoff plot.Keywords: Adsorption, Azo dye, Bentonite, Isotherm, kinetic.